The Influence of strategic planning practices in crisis management by selected organizations in the service industry in Nairobi County - Kamani, Judith Mukami (Strathmore University, 2021)
Strategic planning practices are management practices which involve the creation of future objectives and identification of programs necessary to achieve the organizations goals and create controls to monitor and implement the company’s strategies. The research focused on the ideal principal that organizations within the service industry in Nairobi should have a blueprint through its strategic plans on how to manage a crisis situation in order to maintain a competitive advantage within the industry. The specific objectives of the study was to establish the influence of personnel training, pre-set guidelines and contingency planning had in crisis management in service organizations in Nairobi. The study utilized the three theories of contingency planning theory, crisis management planning model and business planning theory. Judgmental sampling technique was used to select respondents working in the service industry within the Nairobi county. Data was analyzed using SPSS, descriptive statistics, correlation analysis and regression analysis. The study demonstrated that there is a strong, positive and significant relationship between the independent variables of personnel training, pre- set guidelines and contingency fund and the dependent variable of crisis management. The study concludes that while organizations have identified various internal facets that protect them from the negative effects that comes with crisis situations, companies today still need to take bolder steps in managing their strategic planning practices.
A Thesis submitted in partial fulfillment of the requirement for the Degree of Master of Commerce at Strathmore University
Keywords: Strategic planning practices; Crisis management; Service industry_Nairobi County